Assessing gibberellins oxidase activity by anion exchange/hydrophobic polymer monolithic capillary liquid chromatography-mass spectrometry. - Ming-Luan Chen (Public Library of Science (PLoS), 2013)
Bioactive gibberellins (GAs) play a key regulatory role in plant growth and development. In the biosynthesis of GAs, GA3-oxidase catalyzes the final step to produce bioactive GAs. Thus, the evaluation of GA3-oxidase activity is critical for elucidating the regulation mechanism of plant growth controlled by GAs. However, assessing catalytic activity of endogenous GA3-oxidase remains challenging. In the current study, we developed a capillary liquid chromatography--mass spectrometry (cLC-MS) method for the sensitive assay of in-vitro recombinant or endogenous GA3-oxidase by analyzing the catalytic substrates and products of GA3-oxidase (GA1, GA4, GA9, GA20). An anion exchange/hydrophobic poly([2-(methacryloyloxy)ethyl]trimethylammonium-co-divinylbenzene-co-ethylene glycol dimethacrylate)(META-co-DVB-co-EDMA) monolithic column was successfully prepared for the separation of all target GAs. The limits of detection (LODs, Signal/Noise = 3) of GAs were in the range of 0.62-0.90 fmol. We determined the kinetic parameters (K m) of recombinant GA3-oxidase in Escherichia coli (E. coli) cell lysates, which is consistent with previous reports. Furthermore, by using isotope labeled substrates, we successfully evaluated the activity of endogenous GA3-oxidase that converts GA9 to GA4 in four types of plant samples, which is, to the best of our knowledge, the first report for the quantification of the activity of endogenous GA3-oxidase in plant. Taken together, the method developed here provides a good solution for the evaluation of endogenous GA3-oxidase activity in plant, which may promote the in-depth study of the growth regulation mechanism governed by GAs in plant physiology.